2004
DOI: 10.1016/s0926-6410(04)00037-0
|View full text |Cite
|
Sign up to set email alerts
|

Emotion?attention network interactions during a visual oddball task

Abstract: Emotional and attentional functions are known to be distributed along ventral and dorsal networks in the brain, respectively. However, the interactions between these systems remain to be specified. The present study used event-related functional magnetic resonance imaging (fMRI) to investigate how attentional focus can modulate the neural activity elicited by scenes that vary in emotional content. In a visual oddball task, aversive and neutral scenes were presented intermittently among circles and squares. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
46
1
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(54 citation statements)
references
References 31 publications
6
46
1
1
Order By: Relevance
“…This is suggested by our observation that we did not observe any DMPFC activation during the preceding expectancy period. This is further supported by analogous findings in recent studies who also observed DMPFC involvement only during attention to pictures but not in the preceding period [Bermpohl et al, 2006a,b] as well as by studies on simultaneous attention [Fichtenholtz et al, 2004;Keightley et al, 2003;Lane et al, 1999;Liberzon et al, 2000;Pessoa et al, 2002;Winston et al, 2003]. This suggests that the DMPFC is specifically involved in attending stimulus perception and its associated mental states rather than being recruited by attention, i.e., expectancy, itself.…”
Section: Process-specificity and The Dmpfcsupporting
confidence: 87%
See 1 more Smart Citation
“…This is suggested by our observation that we did not observe any DMPFC activation during the preceding expectancy period. This is further supported by analogous findings in recent studies who also observed DMPFC involvement only during attention to pictures but not in the preceding period [Bermpohl et al, 2006a,b] as well as by studies on simultaneous attention [Fichtenholtz et al, 2004;Keightley et al, 2003;Lane et al, 1999;Liberzon et al, 2000;Pessoa et al, 2002;Winston et al, 2003]. This suggests that the DMPFC is specifically involved in attending stimulus perception and its associated mental states rather than being recruited by attention, i.e., expectancy, itself.…”
Section: Process-specificity and The Dmpfcsupporting
confidence: 87%
“…Phan et al [2002] therefore conclude that the DMPFC is engaged in implicit cognitive aspects of emotion processing that are common across emotional tasks. Recent results indicate that this implicit cognitive function may be the specific attentional modulation of emotional stimulus processing [Bermpohl et al, 2006a;Fichtenholtz et al, 2004;Keightley et al, 2003;Lane et al, 1999;Liberzon et al, 2000;Nitschke et al, 2006;Pessoa et al, 2002;Ueda et al, 2003;Winston et al, 2003]. This suggests that neural activity in the DMPFC is characterized by a specific process within a particular domain.…”
Section: Introductionmentioning
confidence: 99%
“…First, we did not have specific network hypotheses regarding the causal implication of the dorsal stream in the type of emotional modulation under study. Second, it appears that modulation of the dorsal stream by emotional competence is weak (Fichtenholtz et al, 2004). Accordingly, we did not find strong evidence of modulation of activity by the emotional competence of the stimuli in high-order areas associated with the dorsal visual stream using distributed source reconstruction.…”
Section: Definition Of Rois and Null Model For The Dcm Analysiscontrasting
confidence: 68%
“…From an evolutionary standpoint, organisms benefit from having a mechanism by which highly arousing stimuli can capture attention (Öhman and Mineka, 2001). Indeed, studies that employ emotional stimuli often show an interaction between attention and emotion in the dACC (Carlsson et al, 2004;Fichtenholtz et al, 2004) and experimental tasks that explicitly manipulate attention towards emotion robustly engage the dACC (Hutcherson et al, 2005;Lane et al, 1997a;Taylor et al, 2003).…”
Section: Discussionmentioning
confidence: 99%